Investigation of error performance in OFDM with network coding techniques in multiple relay networks - Ngu War Hlaing (sciendo, 2020)
The aim of this paper proposes an orthogonal frequency-division multiplexing (OFDM) with network coding to improve the error performance of the system when the messages are transmitted from user to receiver. Two-way relay (TWR) networks are applied to reduce the transmission time slots. The exclusive-OR (XOR) coding is used for network coding in which source nodes exchange their information via TWR nodes. The XOR coded bits provides redundancy to achieve the transmit diversity gain which improves the error performance of the TWR network. OFDM is exploited for TWR to obtain the frequency selective fading nature of wireless channels. The different modulation schemes such as Quadrature Phase Shift Keying (QPSK), 16-Quadrature Amplitude Modulation (QAM) and 64-QAM with OFDM system are simulated and QPSK is selected as it gives the lowest bit error rate (BER). The multiple relaying schemes with different numbers of the information packets are also considered in this paper. Simulation results show that multiple relay schemes provide faster transmission time and better error rate performance. Moreover, different kinds of channel coding schemes such as Convolutional, Reed-Solomon (RS) and turbo codes are applied in OFDM system with network coding to compare and evaluate the BER performance of the proposed system. From the simulation results, network coded OFDM scheme with turbo codes give better BER performance for given Signal-to-Noise Ratio (SNR) in relaying scheme with different numbers of information packets compared to those of convolutional and RS codes. It shows that, the error rate performance and transmission time is reduced 10 percent than the conventional scheme at even at low SNR value.